2015
DOI: 10.2147/ppa.s82441
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quality of health care services among people with osteoarthritis – results from a nationwide survey

Abstract: ObjectiveTo assess the perceived quality of care received by people with osteoarthritis (OA) in Norway and explore factors associated with the quality of care.MethodsA national survey in which members of the Norwegian Rheumatism Association with OA registered as their main diagnosis completed a questionnaire. The perceived quality of care was reported on a 17-item OsteoArthritis Quality Indicator questionnaire, covering both pharmacological and non-pharmacological aspects of OA care. In addition, the four-page… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 14 publications
(17 reference statements)
5
30
4
Order By: Relevance
“…Compared to a previous study in people with only knee OA including subsamples from Denmark, UK and Portugal, the mean total pass rate in the current study was higher than the Danish, but lower than the Portuguese and UK median pass rates 11 . The proportion of females in the current study was somewhat higher compared to three previous Norwegian studies 4,9,10 . The female predominance may be a result of a combination of the higher OA prevalence among females 1 and of females being more willing to participate in patient education programmes, which is also shown in previous research 24 .…”
Section: Discussioncontrasting
confidence: 82%
“…Compared to a previous study in people with only knee OA including subsamples from Denmark, UK and Portugal, the mean total pass rate in the current study was higher than the Danish, but lower than the Portuguese and UK median pass rates 11 . The proportion of females in the current study was somewhat higher compared to three previous Norwegian studies 4,9,10 . The female predominance may be a result of a combination of the higher OA prevalence among females 1 and of females being more willing to participate in patient education programmes, which is also shown in previous research 24 .…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast to two previous studies, which showed that age, gender, education and severity of the OA disease were related to QI achievement, 13 14 patient characteristics in the present study were not associated with QI achievement. The median percentage of QIs achieved for the total study sample was similar to the rates in two previous studies of patient-reported OA QI achievement rates in primary healthcare, 24 27 34 higher median than in three studies 14 20 28 and lower median than in one study. 26 It has previously been shown that adherence to QIs in OA care was lower compared to that in gout or other chronic conditions in older adults.…”
Section: Discussionsupporting
confidence: 82%
“…Notwithstanding the publication of guidelines, there still appears to be a large gap between best practice as defined by scientific evidence and actual clinical care in knee OA as shown from several studies in different countries . A recent Norwegian study showed that guideline adherence to nonpharmacological treatment modalities was only 44% . Adherence to guidelines can be assessed with quality indicators, which are measurable elements in the diagnostic and therapeutic process and based on scientific evidence or consensus .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] A recent Norwegian study showed that guideline adherence to nonpharmacological treatment modalities was only 44%. 13 Adherence to guidelines can be assessed with quality indicators, which are measurable elements in the diagnostic and therapeutic process and based on scientific evidence or consensus. 14,15 A set of 21 quality indicators for the management of OA was developed for the Belgian primary health care system.…”
Section: Introductionmentioning
confidence: 99%